312 Skeletal muscle contractile properties before, during and after muscle injury in male professional football players. (3rd March 2020) - Jones, Ashley; Hind, Karen; Jones, Gareth; Wilson, Hannah V; Francis, Peter
Abstract : Background: Muscle injuries represent over 40% of all injuries reported in professional football. The assessment and monitoring of muscle contractile properties is used in footballers to determine the muscular response to injury and rehabilitation. Objective: To determine changes in muscle contractile properties from baseline (pre-season) to immediately after injury and prior to the point of return to play (RTP). Design: An observational study design was used during the English Football League 2016–17; 2017–18; 2018–19 seasons. Setting: Male English Professional Football Patients (or Participants): A total of 193 players from northern professional football clubs within ∼1hour of the university had muscle contractile players assessed during pre-season. A sub-sample of these players sustained an injury (n=14; age: 23.4±5.7 years, height: 180.0±8.6 cm, body mass: 77.2±7.5 kg). Interventions (or assessment of risk factors): Muscle contractile properties were measured during pre-season, within 5 days of a muscle injury occurring and within 2 days of a player returning fitness that allowed inclusion in the match day squad. Main outcome measurements: Muscle contractile properties were assessed using TMG (GK 40, Panoptik d.o.o., Ljubljana, Slovenia). The following muscles were assessed: Adductor Magnus (AM), Bicep Femoris (BF), Gastrocnemius Lateralis (GL), Gastrocnemius Medialis (GM), Gluteus Maximus (GT) and Rectus Femoris (RF). Maximal muscle displacement (Dm) and contraction time (Tc) were obtained for each muscle. Results: Relative to baseline measures, the median Dm was lower immediately after injury (-11%, P =0.014) and higher following rehabilitation (+33%, P =0.001). Injury and rehabilitation influenced Tc ( P <0.05) but there was no consistent trend in either direction. Conclusions: Dm is a non-invasive measure of the stiffness or tone of the muscle and appears to be sensitive to detect changes due to injury and intervention in professional football players.